2021
DOI: 10.1186/s13005-020-00253-z
|View full text |Cite
|
Sign up to set email alerts
|

Application value of combination therapy of periodontal curettage and root planing on moderate-to-severe chronic periodontitis in patients with type 2 diabetes

Abstract: Background Our study attempted to observe the value of periodontal curettage combined with root planing on moderate-to-severe chronic periodontitis in patients with type 2 diabetes. Methods There involved 72 patients with type 2 diabetes mellitus complicated with moderate-to-severe chronic periodontitis who were diagnosed and treated in our hospital from January 2019 to December 2019. The patients enrolled were randomly divided into four groups usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In this randomized clinical trial with a 3-month follow-up, adjuvant use during initial therapy resulted in similar clinical periodontal improvements compared with mechanical therapy alone. These results are consistent with many studies (Camargo et al 2013;Raman et al 2014;Gay et al 2014;Bian et al 2021) and confirm the effectiveness of non-surgical mechanical procedures in the treatment of periodontitis. On the other hand, there was no significant difference between the test group and the control group during the follow-up period.…”
Section: Discussionsupporting
confidence: 92%
“…In this randomized clinical trial with a 3-month follow-up, adjuvant use during initial therapy resulted in similar clinical periodontal improvements compared with mechanical therapy alone. These results are consistent with many studies (Camargo et al 2013;Raman et al 2014;Gay et al 2014;Bian et al 2021) and confirm the effectiveness of non-surgical mechanical procedures in the treatment of periodontitis. On the other hand, there was no significant difference between the test group and the control group during the follow-up period.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the association of periodontitis and systemic disease, Bian et al assessed the influence of NSPT on CRP levels in patients with periodontitis and type-2 diabetes mellitus [32]. Our study showed that 3 months after NSPT, CRP levels decreased significantly, suggesting that CRP is also influenced by liver stress status.…”
Section: Discussionmentioning
confidence: 50%
“…There is insufficient literature to compare the effectiveness of ENAP over curettage.According to Yukna et al, the ENAP tends to higher reduction in periodontal pocket because of the complete eradication of the sulcular epithelium and the potential for soft tissue attachment to the tooth, which was evidenced in the present study. Histological investigations show that the mode of this attachment is most likely a long junctional epithelium 8 .Bian et al stated that combination therapy of curettage and root planing therapy elicited valid effects in terms of reducing PI, GI, PDin his study 9 . Harsas et al also reported reduction in probing pocket depth which was similar to the present study 10 .Also, kumari et al, in a study revealed reduction in PI, GI, BOP, PPD and gain in clinical attachment level in the sites treated with ENAP 11 .Gudakuwala et al in a study stated that there was reduction in PI, GI, PPD and gain in clinical attachment level in the sites treated with ENAP which was similar to the present study 12 .…”
Section: Discussionmentioning
confidence: 89%